The Tragedy of Alzheimer's Disease: Towards Better Management via Resveratrol-Loaded Oral Bilosomes - Haidy Abbas; Heba A. Gad; Mohamed A. Khattab; Mai Mansour (MDPI AG, 2021)
Alzheimer's disease (AD) is a neurodegenerative disease where oxidative stress plays a major role as a key pathologic factor. The study aims to develop resveratrol (RES)-loaded bilosomes for oral use, aiming to enhance RES bioavailability. RES-loaded bilosomes were prepared using the thin-film hydration technique. The effect of different formulation variables viz. the number of extrusion cycles, drug concentration and the effect of pH of the medium and cholesterol addition on the physicochemical properties of the prepared bilosomes was investigated. Results revealed the successful entrapment of RES into bilosomes. An optimized formula was selected, showing the lowest particle size (189 ± 2.14), acceptable PDI (0.116) and entrapment efficiency (76.2 ± 1.36). In vivo studies on a streptozotocin-induced animal model of AD showed the preeminence of bilosomes over traditional drug suspension to enhance mice memory via Y-maze and Morris water maze tests. Moreover, mice treated with the optimized formula exhibited decreased COX2, IL-6, amyloid-beta peptide and Tau protein levels compared to the drug suspension. Immuno-histochemical analysis revealed a significant decrease of glial fibrillary acidic protein values and microglial cell count in mice treated with bilosomes. Finally, it could be advocated that RES-loaded bilosomes could be a promising drug delivery system to control AD.